Sisters in law [compact disc, unabridged] : how Sandra Day O'Connor and Ruth Bader Ginsburg went to the Supreme Court and changed the world - Hirshman, Linda R. (Harper Collins Publishers, 2015)
The relationship between Sandra Day O'Connor and Ruth Bader Ginsburg, Republican and Democrat, Christian and Jew, western rancher's daughter and Brooklyn girl, transcends party, religion, region, and culture. Strengthened by each other's presence, these groundbreaking judges, the first and second to serve on the highest court in the land, have transformed the Constitution and America itself, making it a more equal place for all women.